The Ontology of the Digital Bible: A Theological Critique of Computational Hermeneutics - Zakaria Zakaria; Ibiang O. Okoi (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
The digitization of the Bible has marked a pivotal transformation in Christian engagement with the text since the Reformation; however, its theological ramifications remain inadequately explored. The paper is a critical analysis of how computational interfaces, such as the biblical applications to algorithmic study tools, are changing the ontology and hermeneutics of Scripture. Informed by theology, bibliology, media theory, and historical textual analyses, we argue that digital spaces pose a risk to reducing the Bible as a tool of divine interaction to religious information, emphasizing fragmentation over canonical understanding, algorithmic suggestions over ecclesiastical wisdom, and searchability over thoughtful reading. The present paper will analyze case studies of well-known online Bible platforms (YouVersion, Logos, and machine-generated Bible interpretation tools) to show how interface choices (such as isolating verses, hyperlinking structures, and the presence of machine-generated interpretation) reflect certain theological assumptions, which, in most cases, go unchallenged. Such advancements have raised urgent questions about the sacramental character of Scripture, the role of tradition in interpretation, and the nature of revelation in the age of computational mediation. This essay is a critique of technological reductionism and, without lapsing into reactionary technophobia, offers some principles of more authentic digital interaction, such as designs that are contextually sound, reveal algorithmic partiality, and restore contemplative slowness. These considerations complement the discussion at the intersection of digital humanities and theological hermeneutics and provide practical advice on how churches to which the biblical practice turns digital can be guided.